Assessment of the change in cetuximab‐induced antibody‐dependent cellular cytotoxicity activity of natural killer cells by steroid. Issue 3 (26th May 2015) - Kumai, Takumi; Oikawa, Kensuke; Aoki, Naoko; Kimura, Shoji; Harabuchi, Yasuaki; Kobayashi, Hiroya
Abstract: Background: Epidermal growth factor receptor (EGFR)‐targeted therapy has been widely accepted as a promising treatment for solid tumors. Steroid treatment is used to prevent adverse effect of anti‐EGFR antibody; however, influence of steroids in the antitumor activity of targeted antibody remains poorly understood. Herein, we demonstrated the impact of steroids in induced antibody‐dependent cellular cytotoxicity (ADCC) activity of natural killer (NK) cells by cetuximab. Methods: Various numbers of NK cells from healthy donors were co‐cultured with tumor and/or cetuximab with or without dexamethasone. After incubation, NK cells, ADCC activity, survival, and activation markers expression were determined. Results: Clinical concentration of dexamethasone treatment clearly inhibited cetuximab‐induced ADCC activity of NK cells against head and neck squamous cell carcinoma (HNSCC) and colon cancer. Dexamethasone decreased the activation marker CD69 expression on NK cells. Conclusion: This is the first report that shows the negative affect of steroids in cancer treatment using therapeutic antibody. Attention needs to be paid for using steroids in tumor treatment. © 2015 Wiley Periodicals, Inc. Head Neck 38: 410–416, 2016